Schwartz - Jampel syndrome - Bastola, P (Kathmandu University Medical Journal, 2012)
This is a report of a very rare case of Schwartz Jampel syndrome, with few unusual findings, in a 13 years girl from Nepal, who concurrently also had superotemporal subluxation of the crystalline lens along with blepharophimosis syndrome. DOI: http://dx.doi.org/10.3126/kumj.v8i3.6227 Kathmandu Univ Med J 2010;8(3):348-51